Biodegradable biocomposite starch based films blended with chitosan and whey protein - Fauziah Shaheen, Sheh Rahman (2010)
The use of synthetic plastic materials as a food packaging causes serious hazards to the environment. The introduction of biodegradable materials, which can be disposed directly into the soil, can be one possible solution to this problem. The objectives of this work were to produce biodegradable biocomposite films and study the characterization of starch-based films blended with chitosan and whey protein. The films were synthesized by using the mixing process and the casting method. The characteristics of the blend films with different tapioca starch composition (1, 2, 3, 4 and 5 g/100 mL) were evaluated using Universal Testing Machine, Fourier transform infrared spectroscopy (FTIR), differential scanning calorimeter (DSC), Thermogravimetric Analysis (TGA), scanning electron microscope (SEM) observation and biodegradability using microbiological degradation test and soil burial degradation test. Among them, the biodegradable blend films compatibilized with 1% of tapioca starch content showed good mechanical properties and had the highest thermal stability. The FTIR confirmed that tapioca starch, chitosan and WPI were compatible and inter-molecular hydrogen bonds existed between them. Moreover, the SEM analysis with 1% of tapioca starch content showed a compatible, smooth and homogenous structure of the composite film. The microbiological degradation test indicated that the growth of A. Niger colony increases as the tapioca starch content was increased. In soil burial test, a rapid degradation occurred for all the films in the initial 10 days followed by 100% composting within 18 days. As a conclusion, the film fabricated had potential application in future to be used as food packaging because it can enhanced foods quality and at the same time protected the environment.